Direct‐space solution in the EXPO package: the combination of the HBB–BC algorithm with GRASP. Issue 2 (30th March 2018) - Altomare, Angela; Corriero, Nicola; Cuocci, Corrado; Falcicchio, Aurelia; Moliterni, Anna; Rizzi, Rosanna
Abstract : The hybrid big bang–big crunch optimization method, already implemented in the last version of the EXPO program, has been combined with the greedy randomized adaptive search procedure (GRASP) and improved. The new procedure aims to solve crystal structures from powder diffraction data. Abstract : The hybrid big bang–big crunch algorithm is a combination of a global optimization algorithm inspired by one of the theories of the evolution of the universe, named the big bang and big crunch theory, and the simulated annealing method. The procedure was implemented in the latest version of the program EXPO and applied to crystal‐structure solution from powder diffraction data. Several aspects of the hybrid big bang–big crunch algorithm can be further optimized with the aim of obtaining good quality solutions in a shorter computation time. In the present study, the hybrid big bang–big crunch procedure has been combined with the greedy randomized adaptive search procedure (GRASP) and some steps of the algorithm have been improved. The new approach, implemented in the EXPO package, has been successfully tested on numerous known crystal structures.